KORELASI ANTARA SKOR SIMTOM DEPRESI DAN KEKUATAN GENGGAMAN TANGAN PADA USIA LANJUT DI PANTI WREDHA DAERAH ISTIMEWA YOGYAKARTA - , AHMAD SYAHRI; , dr. Agus Siswanto, SpPD-KPsi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: By the year of 2020, the elderly population in Indonesia will be expected the fourth highest number in the world after China, India and the USA. Special Region of Yogyakarta in Indonesia has the highest percentage that is equal to 13.72%. Depression may increase the risk of mortality, disability and physical activity motivation. Hand grip strength test is a valid method of examination, consistent and simple to assess muscle strength, and low grip strength can increase mortality and morbidity in the elderly. Objective: This study aimed to assess correlation between depressive symptoms and grip strength in the elderly population in nursing homes at province of Yogyakarta. Methods: A cross-sectional study was conducted in October 2010 at the nursing home residents. Depression was assessed by the Geriatric Depression Scale 30 Cronbachâs alpha 0,88. Handgrip strength was measured with a handgrip dynamometer. Data of age, education, gender was collected by questionnaire. We performed statistical tests to assess the correlation of symptoms of depression and grip strength. Results: The mean age of subjects was 73.84 Â± 8.36 years with 36 subjects (35.3%) were between 60-69 years and 66 subjects (64.7%) were over 70 years. There were 33 men (32.4%) and 69 women (67.6%). Mean GDS score was 12.76 Â± 3.22. Handgrip strength in the depression group 16.94 Â± 6.96 kg, higher than the non-depressed group 15.23 Â± 6.79. There is correlation between severity of depression symptom with handgrip strength with r = 0.235 (weak correlation) and significant by statistically p = 0.017. Conclusion: The severity of depressive symptom scores it was correlated significantly to the handgrip strength in elderly nursing homes in the province of Yogyakarta.